2019
DOI: 10.21926/obm.icm.1903052
|View full text |Cite
|
Sign up to set email alerts
|

Does a Single Bout of Aerobic Exercise Improve Set Shifting in Healthy Young Adults? A Systematic Review and Meta-Analysis

Abstract: This systematic review and meta-analysis investigated whether acute aerobic exercise improves subsequent set shifting performance in healthy young individuals. Potential moderation of studies' methodological quality and exercise intensity, as well as the presence of small-study effect was also examined. Studies were identified using electronic databases Medline, PsycINFO, and SPORTDiscus, as well as references of recent meta-analyses and references of included studies. In total, 12 studies were included into q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(100 reference statements)
0
0
1
Order By: Relevance
“…This further supports our assumption of the linkage between OSE and executive function. However, the opposite result was shown in a previous study [ 65 , 66 ]. Morava et al [ 65 ] found no effect after a single bout of aerobic exercise in task-switching performance under pressure situations.…”
Section: Discussioncontrasting
confidence: 89%
“…This further supports our assumption of the linkage between OSE and executive function. However, the opposite result was shown in a previous study [ 65 , 66 ]. Morava et al [ 65 ] found no effect after a single bout of aerobic exercise in task-switching performance under pressure situations.…”
Section: Discussioncontrasting
confidence: 89%